A Review on Nanoparticles : The Building Blocks of Tomorrows Technology (International Journal of Scientific Research in Science and Technology, 2024)
Nanoparticles, defined as particles with dimensions in the nanometer range, exhibit unique properties that differ from their bulk counterparts, making them invaluable across various fields such as medicine, electronics, and environmental protection. Their small size and specific characteristics enable advanced applications, including targeted drug delivery, enhanced imaging, and improved sensors. Notable types of nanoparticles include silver, gold, magnetic, iron oxide, and platinum, each with distinct uses: silver for antimicrobial applications, gold for protein detection and drug delivery, magnetic for drug delivery and bio sensing, iron oxide for diagnostics and therapy, and platinum for catalysis. Nanoparticles are synthesized through top-down methods like milling and laser ablation, and bottom-up approaches such as sol-gel and hydrothermal processes. Their preparation involves techniques like emulsion-solvent evaporation and polymerization. Effective characterization, including analysis of size, shape, zeta potential, and drug entrapment efficiency, is essential for optimizing their performance in various applications. The review’s current focus is on the synthesis, types, characterization, and most advanced applications of nanotechnology.